Chromosomal Aberration and Histopathological Effect of Metronidazole-Induced Toxicity in Male Rat (Medico Legal Update, 2020)
One of the most world anti parasitic and antibacterial compound used is Metronidazole (MTZ),all Drugtoxicity must be acceptable to relief patients and should cause less harm to human than infection itself.MTZ is potentially genotoxic to humans due to the following facts: it is a proven toxogenic to human cellsas well as wide range of side effects including chromosomal aberration and reproductive toxicity. The studyis designed to assess the cytotoxic and reproductive toxicity effects of two dose of MTZ (250 mg/kg b.wtgroup and 500 mg/kg b.wt group) orally by gavage for 30 days and compared with control group (givennormal saline) and then examine chromosomes from bone marrow cells and testicular gametogenic activityof adult male albino rats.Evident toxicity of both treatments of MTZ groups on chromosomal aberration (fragment, deletion and ringchromosome),with increased number of polyploid cells which were significantly increased (P< 0.05) by doseand time compared with control group. MTZ significant decrease in sperm activity and in deformed form(P< 0.05) .as well as reduced testes weight, also MTZ stimulate injured in seminiferous tubules especialygerminal epithelium.